Hot forging for producing railway wagon bogie adapter - G. Song; H. C. Ji; W. C. Pei; J. S. Li; S. Cai; B. X. Liu (Metalurgija, 2022)
Hot forging forming of railway wagon bogie adapter is a new railway wagon bogie adapter processing technology. In this paper, a hot forging die for railway wagon bogie adapter was designed, and the forming quality were analyzed by using DEFORM-3D software. Then, the feasibility of the process was verified by experiments. It was found that using this mold can eliminate the defects such as loose as-cast in metal smelting process, optimize the microstructure, forging products with good density, product quality and other characteristics of stability.